Aortic flow patterns in bicuspid aortic valve disease visualised with 4D flow imaging. (24th May 2012) - Gedicke, MM; Pitcher, A; Barker, A; Bock, J; Lorenz, R; Francis, JM; Davis, A; Markl, M; Myerson, SG; Neubauer, S
Abstract : Aims: Bicuspid aortic valve disease (BAV) affects around 1% of the population and is associated with aortic dilation. We examined the difference in aortic flow patterns in different valve leaflet fusion patterns, to determine if the flow pattern might be partly responsible for the aortic dilation through altered wall shear stress. Methods: Cardiac magnetic resonance was used to image time-resolved 3D flow patterns (4D flow) in the ascending aorta of patients with differing types of bicuspid valve in 44 patients with bicuspid aortic valve disease age 13-71 years (male: female 31:13). Results: Of 44 patients with bicuspid aortic valve disease, 29 had a right-left coronary cusp fusion pattern, 12 had a right-non coronary cusp fusion pattern and 3 had left-non coronary cusp fusion pattern (figure 1 ). There were similar flow patterns in each of the three types of bicuspid valve, with a predominantly right-handed helical flow pattern present in 79%, 75% and 67% respectively. Left-handed helical flow was only seen in 2 cases and a complex flow pattern was seen in 4 cases. Normal flow patterns were seen in 4 cases, and all patients with a normal flow pattern had normal ascending aortic diameters (mean 2.6 cm), while those with abnormal flow patterns had larger diameters (mean 3.7 cm); p=0.005. Conclusion: This is the first study showing a predominantly right-handed helical flow pattern in all 3 valve leaflet fusion patterns, with only 2 participants showing a left-handed helical flow pattern. Normal flow patterns were only observed in patients with normal aortic diameters, suggesting that aortic dilation is associated with abnormal helical flow patterns, though whether these are causative needs further research (figure 1).